Effectiveness of rehabilitation training on radiotherapy-related abnormalities of voice function in head and neck cancer patients: A systematic review and meta-analysis. - Mengqin Zhao; Jiaying Yao; Junhui Wang; Xinyi Shen; Tingting Liu; Limin Pu; Ying Li; Xiaomin Chen (PLoS ONE)
Background Abnormal speech function caused by radiotherapy will affect the normal communication of patients with head and neck cancer (HNC) and even interrupt their social life. Rehabilitation Training is widely used to improve articulatory abnormalities in patients with HNC. However, the effectiveness of these rehabilitation measures in restoring the voice function of HNC patients is still unknown. Objective This study aimed to systematically examine the effects of rehabilitation training on radiotherapy-related voice function and quality of life in patients with HNC. Methods The databases PubMed, Web of Science, EMBASE, Cochrane Library, CINAHL, CNKI, Wan Fang, and SinoMed were searched for studies published from inception through October 2024. Randomized controlled trials of rehabilitation training to improve voice function abnormalities associated with radiotherapy for HNC were included, and two investigators independently performed the literature review. Meta-analysis was performed using RevMan 5.4 software to determine statistical heterogeneity based on P-values and I2 values. Results 13 randomized controlled trials involving 710 participants were included. Meta-analysis showed that rehabilitation training significantly affected the patients' maximum phonation time(MD=1.53, 95%CI=[0.83, 2.23], P<0.0001, Grade Moderate), smoothed cepstral peak prominence(MD=-0.59, 95%CI=[-0.89, -0.29], P=0.0001, Grade Moderate), social communication abilities(MD=-2.60, 95%CI=[-5.14, -0.07], P=0.04, Grade Moderate), and quality of life(MD=8.49, 95%CI=[3.06, 13.92], P=0.002, Grade Moderate). Conclusions Rehabilitation training is an effective approach for ameliorating abnormal voice functions after radiotherapy for HNC. However, there is no consensus on the optimal frequency, periodicity, and follow-up of interventions for rehabilitation training. More studies are still required to determine the optimal intervention effect for ameliorating speech function abnormalities in patients with HNC after radiotherapy.